Menelisik Perkawinan Adat Belitung Dalam Perspektif Kebudayaannya: Studi Kasus Prosesi Perkawinan Adat Belitung Hingga Perubahan Zaman - Annisa; Ahmad Ruslan; Desvian Bandarsyah (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2021)
Mutus paham is a family of women and men who know each other, and every parent is more stable about his prospective son-in law, then the marriage habit is continued with Mutus Paham, which is a wedding ceremony, at the Mutus Paham ceremony the parents of the bride and groom visit the bridegroom`s house men. They will hold a meeting to determine the date of the marriage contract (consent granted). Mutus paham activities are carried out at night, so people who work can also attend Mutus Paham activities are carried out at night, so people who work can also attend Mutus Paham activities. In Mutus Paham signifies that in the belitong Melayu Marriage Tradition applicants are women. If Jajak Gede is accepted by the male family, the the women`s proposal is accepted and returned by the man by giving the bride (usually clothes). A wedding in Belitong is a place where the groom waits to be picked up by the bride. When taken by the bride, the groom hands over the tipa. Tipa is a box containing money that is kept behind a flowerarrangement as an expression of the pleasure of having a wife. The method that I do is using a literature study.